Phylogenetic analysis of different breeds of domestic chickens in selected area of Peninsular Malaysia inferred from partial cytochrome b gene information and RAPD markers - Jayaraj V.K; Fook Choy Yap; Yap Jin Yan; Kiung Teh Loon; Justina Lee Ning Zhen; Nelly Warau Kamau (2010)
The present investigation was carried out in an attempt to study the phylogenetic analysis of different breeds of domestic chickens in Peninsular Malaysia inferred from partial cytochrome b gene information and random amplified polymorphic DNA (RAPD) markers. Phylogenetic analysis using both neighbor-joining (NJ) and maximum parsimony (MP) methods produced three clusters that encompassed Type-I village chickens, the red jungle fowl subspecies and the Japanese Chunky broilers. The phylogenetic analysis also revealed that majority of the Malaysian commercial chickens were randomly assembled with the Type-II village chickens. In RAPD assay, phylogenetic analysis using neighbor-joining produced six clusters that were completely distinguished based on the locality of chickens. High levels of genetic variations were observed among the village chickens, the commercial broilers, and between the commercial broilers and layer chickens. In this study, it was found that Type-I village chickens could be distinguished from the commercial chickens and Type-II village chickens at the position of the 27th nucleotide of the 351 bp cytochrome b gene. This study also revealed that RAPD markers were unable to differentiate the type of chickens, but it showed the effectiveness of RAPD in evaluating the genetic variation and the genetic relationships between chicken lines and populations.